Robust blood flow velocity estimation from 3D rotational angiography - Bögel, Marco; Gehrisch, S.; Redel, T.; Rohkohl, C.; Birkhold, A.; Hölter, Philip; Maier, Andreas; Kowarschik, M.; Dörfler, Arnd (Proceedings - International Conference on Image Processing, ICIP, 2018)
Blood flow velocity estimation techniques from 2D fluoroscopy and more recently rotational angiography images represent a topic of wide interest in various clinical research areas. In particular, they can be an important step towards patient-specific flow simulations. Additionally, it can be of diagnostic interest to evaluate volumetric blood flow in stenotic vessel segments; e.g. in a patient's brain. In this work, we present a robust optimization-based approach to estimate mean blood flow velocities from rotational digital subtraction angiography (DSA) images. Our method was extensively evaluated on 70 simulated datasets and 6 clinical datasets with MR phase contrast ground truth data. Our evaluation explores the limitations of image-based velocity estimation; i.e., measurements over short or small vessel segments. Overall, we were able to estimate the mean velocity with average errors as little as 4% for simulation studies, if the vessel segment is sufficiently long, and achieved results within the confines of the MR phase contrast ground truth data for our clinical data, with an average relative error to the centerline measurement of 9.5%±10.5%. The achieved accuracy enables patient-specific hemodynamic simulations and may also be of immediate diagnostic interest.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Angiography; Contrast medium; Flow quantification; Velocity estimation